2013
DOI: 10.1007/s10900-013-9722-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Community Health Program in Improving Diabetes Knowledge in the Hispanic Population: Salud y Bienestar (Health and Wellness)

Abstract: We evaluated the effectiveness of the Salud y Bienestar program to deliver diabetes education in the Hispanic population in the United States. This program uses a community outreach model where community health promoters are trained and then they deliver education to other community members regarding diabetes disease, risk factors, and ways to prevent and control disease. This intervention applies a one-group pre- and post-test design to improve diabetes knowledge. The intervention carried out in the states of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…In many countries, the diabetic education programs are implemented to improve diabetic knowledge, attitude and practices to reduce diabetic complications and costs. However, increasing the knowledge by itself may not be necessarily effective in promoting diabetic practices and management outcomes as shown in some studies (5,15,16,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, the diabetic education programs are implemented to improve diabetic knowledge, attitude and practices to reduce diabetic complications and costs. However, increasing the knowledge by itself may not be necessarily effective in promoting diabetic practices and management outcomes as shown in some studies (5,15,16,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…We define CHW as a member of the patient’s community being utilized in any of the aforementioned capacities but not formally trained as a clinical or healthcare professional. Community health workers have been shown to augment patient knowledge [22], improve clinical outcomes [23, 24], reduce disparities [25], and decrease costs [26] in diabetes care. One study even showed increased Medicaid savings when CHWs specifically matched patient needs to local resources [4•].…”
Section: Methodsmentioning
confidence: 99%
“…A randomized control trial of Hispanic-American diabetics living in Dallas supported the effectiveness of education from a promotora in addition to clinicians at reducing subjects HbA1C. Prezio et al (2013) Another quasi-experiment supporting the use of community health workers was conducted among patient populations of three community-based health organizations in Texas, California, and Washington, D.C (Cruz, Hernandez-Lane, Cohello, & Bautista, 2013). Researchers trained community health workers or promoters over three days and created a curriculum with a training manual and tools for community health workers to use with study subjects.…”
Section: Community Lay Health Workersmentioning
confidence: 99%
“…Researchers and clinicians have tried various strategies in recent decades to lessen this growing area of health concerns for our nation's fastest growing demographic. Both Toobert et al (2011) and Rosal et al (2011) (Cruz et al, 2013;Hurtado et al, 2014;Prezio et al, 2013). Some of the latest innovations in teaching diabetes self-management include the use of mobile health devices (Sanjay Arora et al, 2014;Heisler et al, 2014); potential success of these types of interventions should only increase as more and more Americans are using smart phones and have home access to internet.…”
Section: Implications Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation